Formulasi Elixir Pracetamol Dengan Perbedaan Jumlah Co-Solvent Etanol 95% - Nur Dya Puspitasari; Janatun Na'imah (Universitas Muhammadiyah Gresik, 2023)
Paracetamol is a non-opioid pain reliever indicated for headache, transient muscle aches, premenstrual pain and fever. Paracetamol taken orally is well absorbed in the gastrointestinal tract. Drugs in the form of elixir will be easier to consume and will speed up their absorption. This study aims to determine the best paracetamol elixir formula with different amounts of ethanol cosolvent. The evaluation results showed that the paracetamol elixir formulation with different amounts of cosolvent ethanol 95% fulfilled the organoleptic test parameter requirements, pH, hedonism, viscosity and specific gravity. Based on the results obtained, it shows that the elixir preparation at FII is the best preparation because based on the pH test, the results are according to specifications, namely on the zero day, while on the seventh day, the pH is 6. Based on the organoleptic test, the elixir FI and FII preparations were quite stable because they did not change color, smell and taste on day zero and day seven. And based on the hedonism test, the Elixir FII preparation was very liked by respondents from the parameters of color and taste.